Attachment Styles, Personality, and Frustration Intolerance - Christian Schetsche; Alba E. Mustaca (Health Psychology Research)
The objective of the present study was to evaluate the relationships between attachment styles, personality traits, and their effects on frustration intolerance (FI) in a sample of 300 adults. The Argentine Attachment Styles Scale, the Eysenck Revised Personality Questionnaire (EPQ-RA), and the Frustration Intolerance Scale (EIF) was used. In the two Full Latent Variable Models developed, it was determined that neuroticism and avoidant attachment had the greatest mediating effects on FI. Avoidant attachment stood out for its mediating effect on anxious attachment. These two factors were found to explain a considerable percentage of neuroticism and, as a consequence, the four dimensions of FI. It is concluded that it is necessary to reinterpret certain concepts of neuroticism and study them from a perspective that starts from attachment theory.